Knowledge and Practices of Stroke Survivors Regarding Secondary Stroke Prevention, Khomas Region, Namibia - Amukugo Hans Justus, Jachi Peter, (Journal of Medical Biomedical and Applied Sciences, 2016)
The purpose of this study were in two fold namely to determine the knowledge, practices and, challenges as well as the information sources of stroke survivors and also educational practices by stroke management team with regard to secondary stroke prevention, Khomas Region, Namibia.A quantitative, descriptive and explorative design was used. Data was collected from (n=8) stroke management team members and (n=60) stroke survivors discharged stroke survivors from the Katutura State Hospital, in year 2012. Collected data was analysed using Epi Info statistical package version 5.3.1.Although the stroke management team participated in this study acknowledged that they played a role in the health education of stroke survivors with regard to prevention of secondary stroke, it appears that Knowledge and practice on secondary stroke prevention among stroke survivors is very low despite the availability information sources available. The study also revealed that half of the stroke survivors who participated in the study were unable to name a single appropriate action to take to prevent secondary stroke. A significant proportion of stroke survivors also continue to smoke and or consume alcohol contrary to expectations and recommendations. Only a relatively small percentage of stroke survivors comply with lifestyle changes prescribed to them such as diet modification and engaging in physical exercise.